PERANCANGAN DAN PEMBUATAN APLIKASI PERENCANAAN AGENDA PEGAWAI UNS BERBASIS FRAMEWORK YII2 TERINTEGRASI DENGAN API UNS - Yudho Yudhanto; Itabella Kurniasari (IJAI (Indonesian Journal of Applied Informatics), 2017)
From the data in simpeg.uns.ac.id Term employees obtained the data civil servants and non-civil servants as much as 3169. Article Search Google PAID many as 1,435 civil servants Educator, Education Non PNS many as 153, as many as 963 education civil servants, and education as Non PNS 618. While period rooms at UNS per unit of less than 10 rooms.Implementation Planning System Application System employees singer agenda can be memeberikan Namely Solutions can be makes it MEMBER meeting to review the agenda of the Meeting Must know attended and received notification sms broadcast through web-based application framework WITH Yii2 And sms broadcast WITH using API UNS.